Plasmid-Mediated Transmission of KPC-2 Carbapenemase in Enterobacteriaceae in Critically Ill Patients - Schweizer, Christian; Bischoff, Peter; Bender, Jennifer; Kola, Axel; Gastmeier, Petra; Hummel, Manfred; Klefisch, Frank-Rainer; Schoenrath, Felix; Frühauf, Andre; Pfeifer, Yvonne (Frontiers in Microbiology, 2019)
Carbapenem-resistant Enterobacteriaceae (CRE) cause health care-associated infections worldwide, and they are of severe concern due to limited treatment options. We report an outbreak of KPC-2-producing CRE that was caused by horizontal transmission of a promiscuous plasmid across different genera of bacteria and hospitals in Germany. Eleven isolates (8 Citrobacter freundii, 2 Klebsiella oxytoca, 1 Escherichia coli) were obtained from seven critically ill patients during the six months of the outbreak in 2016. One patient developed a CRE infection while the other six patients were CRE-colonized. Three patients died in the course of the hospital stay. Six of the seven patients carried the same C. freundii clone; one K. oxytoca clone was found in two patients, and one patient carried E. coli and C. freundii. Molecular analysis confirmed the presence of a conjugative, blaKPC-2-carrying 70 kb-IncN plasmid in C. freundii and E. coli and an 80 kb-IncN plasmid in K. oxytoca. All transconjugants harboured either the 70kb or 80kb plasmid with blaKPC-2, embedded within transposon variant Tn4401g. Whole genome sequencing and downstream bioinformatics analyses of all plasmid sequences showed an almost perfect match when compared to a blaKPC-2-carrying plasmid of a large outbreak in another German hospital two years earlier. Differences in plasmid sizes and open reading frames point to the presence of inserted mobile genetic elements. There are few outbreak reports worldwide on the transmission of blaKPC-2-carrying plasmids across different bacterial genera. Our data suggest a regional and supraregional spread of blaKPC-2-carrying IncN-plasmids harbouring the Tn4401g isoform in Germany.